The Capitalization Effect of Natural Amenities on Housing Price in Urban China: New Evidence From Changsha - Tuofu, Huang; Qingyun, He; Xiao, Ouyang (Frontiers in Environmental Science, 2022)
This study takes Changsha, an emerging mega-city in China, as a sample to analyze the influence of natural amenity (NA) on housing prices during different periods. We divided the NA into four categories according to their characteristics: Green Space (GS), Wetland Park (WP), XiangRiver Scenic Belt (XR), and green ratio within a community. The housing transaction data is used to calculate the accessibility of a settlement to each NA via the distance. We estimated the influence of NA on housing prices through a geographic weighted regression (GWR), combined with the hedonic theory. Mean values of GWR estimate show the impact and scope of NA on housing prices gradually expanded during years. The most significant effect on housing prices is XR. As the key nature landscape of Changsha, the impact coefficient of XR has risen from 2.34% in 2012 to 5.32% in 2020. WP has a remarkable increase for affecting housing prices, rising from 1.24% to 3.65%. Effect of GS keeps in line during years, at 2.34% to 3.72%. And green ratio’s impact increase from 3.61%to 4.55%. In addition, results reveal the higher range effect of NA on house prices undergoes a spatial expansion from the central urban area to fringe over time, which also implies the capitalization of natural space is becoming more pronounced. Meanwhile, residential communities impacted by NA have a propensity to separate over time. This study provides a different perspective in defining the importance of natural amenities in urban habitat of modern China.